A study of food consumption patterns of children and adults in Ireland : implications for the development of food-based dietary guidelines - Burke, Sarah J. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2006)
Food-based dietary guidelines (FBDG) are guidelines derived from nutrient targets which are translated into food-based guidelines so they can be adopted by the general population. In order for FBDG to be successful, they must be based on the prevailing food and nutrient intakes and set against the cultural context of the country for which they are being developed. The aim of this research was to construct and examine national food consumption survey databases for Irish adults and children for the purposes of examining food consumption patterns with a view to providing key information the formulation ot FBDG.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin